Narrative of the village: centre of the periphery - Jain,Jasbir (Editor) (Rawat Publications, 2006)
Abridged versions of the papers presented in a seminar on 2-4 May 2005; articles chiefly on depiction of the conditon of rural people in India in the fictional works of 20th century Indic authors.